Carbon dot mediated G quadruplex nano-network formation for enhanced DNAzyme activity and easy catalyst reclamation. Issue 71 (17th December 2019) - Kumari, Sonam; Mandal, Saptarshi; Das, Prolay
Abstract : Enhanced DNAzyme activity of G-quadruplex–hemin complex in carbon dot crosslinked nanonetwork with access to easy catalyst regeneration. Abstract : The significant application potential of the DNAzyme activity of G-quadruplex (G4)–hemin complexes has prompted considerable research efforts to amplify their peroxidase mimicking activity to match that of their enzymatic counterparts. However, concurrent improvements in the catalytic cycle and catalyst recovery remain elusive. Herein, we report the creation of a network array of G-quadruplex (G4)–hemin complexes crosslinked by carbon quantum dots (CDs) that not only significantly improves the G-quadruplex–hemin DNAzyme activity, stability, and catalytic cycle, but also points towards easy catalyst regeneration via a semi-heterogeneous catalysis approach. 5′-phosphate terminated G-rich single-stranded DNA molecules proficient in generating intermolecular and intramolecular G-quadruplexes were covalently conjugated to anthrarufin derived CDs through phosphoramidite chemistry. The network array was achieved through K + mediated intermolecular G-quadruplex formation that readily complexes with hemin to give the catalytic core. The presence of CDs in close vicinity ensures a favorable microenvironment that helps in amplifying the DNAzyme activity in both the intermolecular CD–G-quadruplex network assembly and the intramolecular CD–G quadruplex conjugate, while the former is necessary for easy catalyst regeneration. The CD photophysics enable the monitoring of the DNAzyme recovery and reaction progress.